Leaching of Pervious Concrete Produced Using Mixed Recycled Aggregates - Mikami,Rafael Jansen (2020)
Abstract Waste produced by the construction sector is a problem that has grown over the last few years. Construction and demolition waste makes up about 50% by mass of the total solid waste produced in Brazil. One alternative by which to reduce this volume is recycling this material in the form of aggregates. However, it is necessary to analyze the environmental risk that the use of recycled aggregates can entail for adjacent soil and the water table. The purpose of this work was to evaluate pervious concrete samples that contained recycled aggregates and to subject them to leaching tests. The results were compared with the limits established by the Italian methodology. Aggregates with 10, 25, 50, and 100% ceramic were used, as well as a recycled concrete aggregate and a natural aggregate. With the exception of the 25% ceramic trial, all the treatments introduced chromium to the water in which they were immersed, with accumulated concentrations varying from 0.009 to 0.099 mg L-1. Cadmium was found in higher quantities, with cumulated concentrations between 0.104 and 0.417 mg L-1. Sulfate concentrations were higher after 24 h of immersion, with a maximum release of 71.7 mg L-1. The concrete made with 100% ceramic aggregate leached more chromium and sulfate than the other aggregates.